Mortality of the Senior Population – Chorological Perspective - Grzelak-Kostulska, Elżbieta; Hołowiecka, Beata (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The aim of the presented analysis was to update the knowledge on the topic of mortality among senior citizens in Poland. The following article presents a compilation of data concerning mortality rate in relation to various age groups, divided by location and by causes of death. The authors have managed to confirm that the spatial distribution of mortality in relation to various age groups changes in accordance with the specificity of a particular region in respect of the general mortality trend. Higher mortality among younger age groups was noticed in regions with lower life expectancy, whereas, locations with a larger proportion of the old were characterised by the highest values only among senior citizens. It was also proved that together with the transition from one age group to another, the causes of death differ; firstly, cancer dominates, while in the later age deaths are usually caused by the failure of the circulatory system. Moreover, a territorial distribution was confirmed as northern Poland is characterised by higher mortality caused by tumours, while in southern Poland circulatory problems predominate. There are also some regions were those tendencies vary from relatively high to rather low values.